Horticultural therapy for general health in the older adults: A systematic review and meta-analysis - Wang, Zhijie; Zhang, Yu; Lu, Shanshan; Tan, Linlin; Guo, Wei; Lown, Mark; Hu, Xiaoyang; Liu, Jianping (PLOS ONE, 2022)
Background With a pronounced and historically unprecedented tendency of population ageing, research on ageing and related disorders has been increasingly brought into focus. Horticultural therapy (HT), as an important role of social prescribing, has been an integrative for decades. This systematic review and meta-analysis aimed to evaluate HT for general health in older adults. Methods Electronic databases including PubMed, Web of Science, ScienceDirect, the Cochrane Library, MEDLINE (Ovid), EMBASE (Ovid), CINAHL (EBSCO), China National Knowledge Infrastructure (CNKI), and the Wanfang database, grey literature databases and clinical trials registers were searched from inception to March 2021. Randomized controlled trials (RCTs), quasi-RCTs (QRCTs) and the cohort studies about HT for adults aged over 60 were included in this study. Outcome measures were physical function, quality of life, BMI, mood tested by self-reported questionnaire and the expression of the immune cells. The study was registered under PROSPERO (CRD42019146184). Results Totally, fifteen studies (thirteen RCTs and two cohort studies) involving 1046 older participants were included. Meta-analysis showed that HT resulted in better quality of life (MD 2.09, 95% CI [1.33, 2.85], P<0. 01) and physical function (SMD 0.82, 95% [0.36, 1.29], P<0.01) compared with no-gardener; the similar findings showed in BMI (SMD -0.30, 95% [-0.57, -0.04], P = 0.02) and mood tested by self-reported questionnaire (SMD 2.80, 95% CI [1.82, 3.79], P<0. 01). And HT might be conducive on blood pressure and immunity, while all the evidence were moderate-quality judged by GRADE. Conclusions HT may improve physical function and quality of life in older adults, reduce BMI and enhance positive mood. A suitable duration of HT may be between 60 to 120 minutes per week lasting 1.5 to 12 months. However, it remains unclear as to what constitutes an optimal recommendation.